Effectiveness of a Playground Intervention for Antisocial, Prosocial, and Physical Activity Behaviors. (May 2017) - Mayfield, Carlene A.; Child, Stephanie; Weaver, Robert G.; Zarrett, Nicole; Beets, Michael W.; Moore, Justin B.
ABSTRACT: BACKGROUND: We examined the effectiveness of Peaceful Playgrounds™ (P2) to decrease antisocial behaviors (ASB) while increasing physical activity (PA) and prosocial behaviors (PSB) in elementary school children. METHODS: A longitudinal, cluster‐randomized design was employed in 4 elementary school playgrounds where students (third to fifth) from 2 intervention and 2 control schools were observed during recess periods. The intervention included environmental changes (eg, marked surfaces) and student education. Data were collected using systematic observations of youth behavior and semistructured interviews conducted with key informants. Mixed‐effects regression models controlling for scans nested within days nested within schools estimated the interaction of measurement period and treatment condition on children's PA, PSB, and ASB. It was hypothesized that children in intervention, but not control schools, would demonstrate increased PA/PSB and decreased ASB. RESULTS: Contrary to the hypotheses, intervention and control schools showed favorable changes for all dependent variables except for PSB, but 1 intervention and 1 control school drove these effects. Follow‐up interviews indicated variability in implementation and lack of adherence to the control condition. CONCLUSIONS: P2 may promote increased PA during recess, but these results demonstrate the complexity of intervention implementation and the need for rigor when measuring intervention fidelity in real‐world settings.